Neurocognitive determinants of performance variability among world-language users - García, Adolfo Martín (2014)
Although the notion of world language has been variously defined, most accounts acknowledge inter-user performance variability as a key aspect of the construct. The sociocultural aspects of such a phenomenon have been extensively treated in the literature. However, comparatively little attention has been paid to its neurocognitive underpinnings. This paper addresses the biopsychological bases of performance variability among word-language users, focusing on bilingual speakers of English. Available evidence reveals four neurocognitive determinants of variability, namely manner of appropriation, age of acquisition, level of proficiency, and degree of formal similarity between the native and the non-native language. In its concluding section, the paper highlights the benefits of incorporating neurocognitive evidence into the study and conceptualization of world languages.